Antropologi og poetik i Verdenskrøniken 1814 - Michelsen, William (Grundtvig-Studier, 1982)
Anthropology and Poetics in World Chronicle 1814 By Knud Sølvbjerg An exposition by William Michelsen This article is a brief account of the contents of a thesis written in 1976 at the Institute for Scandinavian Studies at Århus University under the title N .F .S . Grundtvig's Thoughts on Anthropology and Poetics between 1814 and 1828. It contains excerpts of a chapter with the same title as this article. The choice of material and the commentary on it has been made by William Michelsen, under whose supervision the thesis was written. The article deals with the considerations concerning mankind and the art of poetry that Grundtvig expresses in his interpretation of mankind’s fate and of the relationship between prophecy and poetry according to the Old Testament. At first these thoughts are set against the idea of all the visible world as an organism with a universal consciousness, as expressed in Henrich Steffens’ introduction to Philosophical Lectures 1803 amongst others. According to Grundtvig, mankind’s development is due not to human reason but to a divine power. And even though Grundtvig’s division of history into three is reminiscent of the division to be found in the concept of the world as an organism, there is no basis for any prediction of history’s development. The pattern which the ancient history of Israel passes on shows how mankind would have developed without the Fall. The divine image is still to be found in mankind and reflects the trinity in God. But the Fall has so confused the inner vision, the emotions and reason that “false images mingled with true images so that the emotions became unclean and reason became ready to judge what it did not understand” (WC 1814 p. 18ff). The Fall in the Garden of Eden, the Flood and the building of the Tower of Babel mark mankind’s step-by-step defection from God. Not until Jesus’ death on the cross did mankind’s relationship with God change for the better. The development in the individual through three stages in which the life of the soul is dominated in turn by the imagination, the emotions and reason also takes place in the individual nation and in the human race as a whole. It is true not merely of the individual but also of the nation and mankind in general that reason is the last faculty to develop. The epistemological consequence is that reason must believe, in the sense that it must believe in the concept of the truthit is to acknowledge. Grundtvig’s idea is that that which at some stage in the future will be recognized, is present beforehand as an imaginative concept. For the nation this means that in the final age it will be able to explain its poetry and its historical achievements on the basis of the previous two. What was once present as a concept returns at the level of reason. History becomes an epistemological process. But without the Bible mankind cannot acknowledge this, according to World Chronicle 1814, inasmuch as Israel’s history is a pattern of the path of history. That is, God does not reveal Himself only in the hearts and consciences of mankind but also in history. But God also reveals Himself in the imagination of the poets - not just amongst the Israelite prophets but also amongst other poets and prophets. For a particularly clear Biblical example of this Grundtvig goes to the story of the prophet Bileam (Numbers 22). Grundtvig does not equate Israel’s prophets with present-day poets, but settles for claiming a likeness between them. He justifies this by pointing to the more powerful imaginations of the ancient prophets, as well as the fact that the Hebrew language had particular qualities because it was closer to the original parent language. Poets should be the people’s guide. After the Fall it is the task of the poet in particular to distinguish between the false and true images that appear to his imagination. According to Grundtvig this cannot be done without the Bible, “unless the poet was inspired in some strange way and became what we call a seer or a prophet”. (WC 1814 p. 167). Bearing recent Grundtvig research in mind it seems surprising how little the passages cited in World Chronicle 1814 have been commented on and utilised to characterise Grundtvig’s poetics. One major reason could be that that they can only be understood in conjunction with Grundtvig’s epistemology and anthropology, which has only recently received a closer examination. It is not enough to see Grundtvig’s poetics as the product of romantic inspiration in a Christian direction. The question is, how was Grundtvig able to combine his experiences as a poet with the Christian faith that he recognised in 1810 to be the only true one. That is the question which this article attempts to answer.